The Unique Morphological Structure of the White Outbred Rat Prostate Gland (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article presents information from local and foreign sources about the anatomical structure, histology, morphogenesis, and characteristic features of the prostate gland of the white outbred rat.